Equations of DC Corona Electric Wind Velocities - Marčiulionis, P.; Žebrauskas, S. (Elektronika ir Elektrotechnika, 2007)
Electrohydrodynamic movement of air is a phenomenon associated with corona discharge. It is widely used in modern technologies. Equations of electric wind in electrode systems with wire corona electrodes are discussed. Difference approximation of the Navier-Stokes equation and the equation of continuity for plane air flow is presented for irregular and regular grids in polar coordinate system. The Coulomb force initiating electric wind is computed analytically using the Deutsch-Popkov assumption. The variation of the force on the axis of symmetry is more significant in comparison with that on the surface of plane electrode. It is the reason of using the polar coordinate system because the grid is regular and of small size in the area near the surface of the wire where the variation of the force is mostly considerable and the values of the force are the greatest. Ill.3, bibl. 9 (in English; summaries in Lithuanian, English and Russian).